2021
DOI: 10.20944/preprints202106.0456.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Some Weather Parameters on Oil Palm Production in the Peninsular Malaysia

Abstract: The effect of some weather parameters (rainfall and temperature) on the production of oil palm in Peninsular Malaysia was investigated. Data were analysed using the Statistical Package for Social Sciences (SPSS 20.0 version), with descriptive statistics, time series analysis, and multiple linear regression (MLR) carried out. SPSS and Microsoft Excel 2010 were used to analyse the results. The MLR model determined the strength of the relationship between oil palm yield (dependent variable) and the changing varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Since the temperature ranged between 25°C and 32°C, our findings revealed that LST temperature was positively correlated with yield. Ahmed et al (2021) agreed with our results, suggesting oil palm achieved the highest yields in areas with a maximum average temperature of 29-33°C and a lowest average temperature of 22-24°C. Apparently, by using backward elimination, rainfall derived from CHIRPS was discovered as a significant predictor compared to rainfall derived from meteorological stations which had low spatial resolution (Orhan et al 2014).…”
Section: Satellite-derived Climatic Variablessupporting
confidence: 93%
See 3 more Smart Citations
“…Since the temperature ranged between 25°C and 32°C, our findings revealed that LST temperature was positively correlated with yield. Ahmed et al (2021) agreed with our results, suggesting oil palm achieved the highest yields in areas with a maximum average temperature of 29-33°C and a lowest average temperature of 22-24°C. Apparently, by using backward elimination, rainfall derived from CHIRPS was discovered as a significant predictor compared to rainfall derived from meteorological stations which had low spatial resolution (Orhan et al 2014).…”
Section: Satellite-derived Climatic Variablessupporting
confidence: 93%
“…Notably, the precipitation collected from CHIRPS dropped precipitously to 170 mm and the land surface temperature was the highest (35°C) in 2015 and 2016 as a result of the very severe El Niño that caused the drought. Possibly, the oil palm yields remained low in the next few years due to the heat stress from the recent very severe El Niño that caused the drought to occur and failed to recover (Khor et al 2021;Ahmed et al 2021). In order to ascertain the results, further verification between ground-based rainfall and temperature and satellite-derived climatic variables will be undertaken.…”
Section: Satellite-derived Climatic Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…require an average rainfall of 150 mm month -1 or 1,750 -3,000 mm year -1 with a dry period of no more than 2 -3 months (Harahap et al, 2013). Rainfall above 2,500 mm is considered unfavorable because it reduces solar radiation (Ahmed et al, 2021). Rainfall of more than 3,500 mm year -1 , less than 2,000 mm year -1 , or less than 100 mm month -1 can also reduce oil palm production and CPO levels (Kamil & Omar, 2017;Woittiez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%